HitSpooling: an improvement for the supernova neutrino detection system in icecube - Heereman von Zuydtwyck, David (Universite Libre de Bruxelles, 2015)
The IceCube Neutrino Observatory consists of a lattice of 5160 photomultiplier tubes (PMTs) which monitor one cubic kilometer of deep Antarctic ice at the geographic South Pole. IceCube was primarily designed to detect neutrinos of energies greater than O(100 GeV). Due to subfreezing ice temperatures, the photomultipliers' dark noise rates are particularly low which enables IceCube to search for neutrinos from galactic supernovae by detecting bursts of MeV neutrinos emitted during the core collapse and for several seconds following. For that purpose, a dedicated online supernova DAQ system records the total number of hits in the detector, without any further information from the PMTs, and generates supernova candidate triggers in case of a significant detector rate enhancement. A new feature to the standard DAQ, called HitSpooling, was implemented in IceCube during this thesis. The HitSpooling system is implemented in the standard DAQ system and buffers the complete raw data stream of the photomultipliers for several hours or days. By reading out time periods of HitSpool data around supernova candidate triggers, generated by the online supernova DAQ system, we overcome the limitations of the latter and have access to the entire information of the detector in case of a supernova. Furthermore, HitSpool data is a powerful source for studying and understanding the noise behavior of the detector as well as background processes coming from atmospheric muons. The idea of HitSpooling was developed in the scope of this thesis and is the basis of the work at hand. The developed interface between the standard DAQ and the supernova DAQ system is presented. The correlated dark noise component in optical modules of IceCube is quantified for the first time and possible explanations are discussed. The possibility of identifying triggering and subthreshold atmospheric muons in HitSpool data and subtracting them from a possible supernova signal is analyzed. Furthermore, the conversion from HitSpool data to supernova DAQ type data ...